A unique presentation of systemic lupus erythematosus in a 7-year-old child - (:unkn) unknown (My University, 1998)
This case report describes a 7-year-old female who presented with lupus nephritis in association with endocrinopathies, central nervous system (CNS) lupus, Libman-Sacks endocarditis which are rare manifestations of this disease in childhood.
Keywords: Central nervous system lupus; Endocrinopathies; Libman-Sacks endocarditis; Systemic lupus erythematosus